PENGARUH PROMOSI TERHADAP PENINGKATAN PENJUALAN PADA PT. COLUMBIA KOTAMOBAGU - PAPUTUNGAN, DESIASTUTY; Tampi, Johny R. E.; Walangitan, Olivia (JURNAL ADMINISTRASI BISNIS, 2017)
To maintain the viability of the company, companies are often faced with the problem, such as the difficulty in increasing the volume of sales of the existence of competition from similar companies increased the complexity of consumer behavior against a product, changing consumer tastes, as well as the uncertain economic conditions. Promotion is an activity that can be done by the company with the aim to inform, persuade, and influence consumers to select or purchase products offered by the company. Promotions at Columbia Kotamobagu PT. is seen from the 6 indicators i.e. advertising, personal selling, sales promotion, public relations, direct marketing tools, measurement scales use the ratin scale. This research is quantitative research using a simple correlation analysis and regression analysis. Data collection techniques in the study was collected in the form of primary data and secondary data, and tools that on the collection of data through a questionnaire filled out by 300 respondents and analyzed using a simple correlation analysis and analysis simple regression. Based on the results of the analysis of simple correlation and simple regression analysis showed that the independent variable is. promotion of the dependent variables simultaneously affecting the increase in sales which means promotion to increased influence sales are still in the low category. It is recommended also to company PT. Columbia Kotamobagu so need to pay attention to the marketing mix policy especially the issue price is set so that the company can be reached by the consumer, so that it can increase the level of sales. Keywords: promotion, increased sales